Supply chain coordination under production yield loss and downside risk aversion. (January 2019) - Cai, Jianhu; Hu, Xiaoqing; Chen, Ke; Tadikamalla, Pandu R.; Shang, Jennifer
Highlights: Consider production yield loss and downside risk aversion. Determine the optimal production quantity from the game leader's perspective. Propose a revenue-sharing contract to coordinate the supplier and the buyer. Jointly achieve supply chain coordination and flexible profit allocation. Abstract: We examine input quantity decisions of a two-echelon supply chain (SC) facing production yield loss and downside risk aversion. We first examine the SC led by the buyer, who aims to maximize the SC's profit. The buyer is downside risk averse and desires to limit the low yield risk for the entire SC. A revenue-sharing contract is introduced to coordinate the SC. We find that an effective SC coordination and an efficient profit allocation can be achieved jointly. When the supplier is a game leader in the SC, the proposed revenue-sharing contract remains effective in coordinating the SC. An extended model considering stochastic demand is further discussed. Numerical studies are conducted to illustrate our models and validate our findings.